Uncertainty in Rock Mass Jointing Characterisation - Lyman, G.; Poropat, G.V.; Elmouttie, M. (SHIRMS 2008: Proceedings of the First Southern Hemisphere International Rock Mechanics Symposium, 2008)
The analysis of jointing in a rock mass is a critical step in any rock engineering project as the extent of fracturing in the rock mass is the dominant factor controlling the rock mass strength.  Uncertainties in the characterisation of a rock mass are very rarely considered.